Resurgent voices on the Israel-Palestine conflict: An appraisal of the alternative pathways towards resolving the conflict - Gada, Muhammad Yaseen (Intellectual discourse, 2016)
This review discusses the changing perceptions and resurgent voices towards the peaceful solution of the Israel-Palestine conflict. The review draws on studies, presented in five recent books, conducted by specialists in the area of (Israel-Palestine) Conflict Resolution and International Studies. The question of whether the two-state solution is still feasible has caused much debate in various academic and public spheres over the last decade or so. The studies, conducted both inside and outside of Israel and Palestine, provide ample support that there have been growing dissenting voices and increasing peaceful resistance against the dominant view of the two-statism that divides territory and segregates the indigenous population with its history of harmony and coexistence. Despite their different views, the authors collectively maintain that in the current milieu of deadlock in the peace process, there is an urgent need to rethink and reformulate the two-state solution that perpetuates the Israeli hegemony and the unleashing of various discriminatory measures against the Palestinian population. Based on some key-common themes pervasive in the works under review, there is ample and growing support to the claim that the one-state solution offers a wider perspective of equal human rights and justice.